DISCURSIVE MECHANISMS OF LEGITIMIZATION: FRAMEWORK FOR ANALYSIS - Zukerstein, Jaroslav (European Scientific Journal, ESJ, 2015)
This paper aims to introduce a framework for interdisciplinary analysis in history, political science and linguistics. When governments pursue a controversial foreign policy and are fully aware of the potential negative domestic and international reception, one of the tools to create consent with the policies is the use of the discursive legitimizing mechanisms. Inspired by Frankfurt school and critical linguistics the paper presents specific mechanisms that could be used for legitimizing problematic foreign policy strategies.